Remote Temperature Monitoring for Infant Incubator using Thermal Camera - Thanaporn Chuenpirom; Kasama Srirussamee; Chuchart Pintavirooj (My University, 2022)
Health concerns over the premature babies are their immature organs and low birth weight. As a result, these babies may have difficulty in breathing, maintaining their healthy body temperature or being light sensitive. Infant incubator has been designed to overcome these issues. It is a medical device that could provide healthy environment, such as light, temperature and humidity. Moreover, it is also able to control and detect any changes which affect the baby’s health. Health monitoring systems are critical in modern incubators, which could involve a set of sensors to read and send physiological information, such as temperature. It has also been proposed that establishing remote monitoring system via global system for mobile communications (GSM) would be beneficial for the incubators as it could send an alarm to the doctors and parents in the event that unhealthy vital parameters have been detected. Although a variety of vital parameters are included in the monitoring features of some modern incubators, the capability to detect body temperature of the babies are limited. Hence, this project proposes the development of an effective low-cost smart infant incubator that will benefit the body temperature monitoring of newborn babies using remote IoT-based monitoring system. The monitoring system is controlled through the use of a Raspberry Pi attached to a visual camera and a thermal IR camera with temperature sensor MLX90640, which was able to measure the body temperature remotely. The software of this smart infant incubator was used to improve monitoring system, which involves image processing techniques. The results of measured ambient temperature were found to be accurate and reliable. The prototypical incubator has been designed and manufactured with affordable cost, and the control system of the incubator was able to work comparably to other incubators with potential capability to measure body temperature of the infant.
Keywords: IoT-based Smart Home Systems